Pollutants Inflow from Btg Ai River and Delok River and Btg Ai Reservoir Outflow and Possible Impact on Aquaculture - Wong, Yik Men (Universiti Malaysia Sarawak, UNIMAS, 2012)
Settlements and developments along the Batang Ai River and Delok River may contribute some pollutants to the water and sediment. Besides that, maintaining water quality and sediment quality are very important to sustain the cage aquaculture activity in Batang Ai Reservoir. Hence, the objective of this study was to investigate the water and sediment quality of Batang Ai River and Delok River and Batang Ai Reservoir. The results obtained from two sampling trips at 5 selected stations indicated that the water quality there was clean which fall in Class II of NWQSM classification. Results for ex-situ water quality parameters are TSS (0.58-8.33 mg/L), BOD5 (3.4-6.61 mg/L), COD (32 – 53.3 mg/L), SRP (0-0.0141 mg/L), TP (0.0193-0.0439 mg/L), NH3-N (0-0.0576 mg/L), NO2-N (0.001-0.007 mg/L), NO3-N (0.01-0.02 mg/L) and TKN (1.216-1.692 mg/L). Nonetheless, the overall water and sediment quality was classified as not possess any negative impacts and damages to the aquatic life and aquaculture activities in the river and reservoir ecosystems.